1,2,4–Thiadiazol-3-Ylthioureas as Synthons for 1,3,5,- Triazinethiones - M. Jollyamma (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
Reduction of 1-aryl-3-(4-aryl-5-arylimino-\(Δ\)2 -1,2,4-thiadiazol-3-yl) thiourea with ammonical hydrogen sulphide yielded 1,3,5-triazine-2-thiones by intramolecular eliminative cyclisation